Computational study of a microwave plasma reactor based on the TM112 mode for diamond deposition - Orozco, E. A.; Tsygankov, P.; Barragan, Y. F.; Hernández, J. A.; Martinez-Amariz, A.; Parada, F. F. (Applied physics. A, Materials science & processing, 2023)
One of the main features of microwave plasma reactors is the electric field structure in the resonant cavity, which must be both intense and uniform in front of the substrate. For this reason, transverse magnetic modes are often used, especially axisymmetric modes because they produce an axisymmetric plasma. Microwave plasma reactors can be differentiated according to the chosen mode, because this has a direct influence on the diamond film growth process, among other features such as the coupling technique and the used quartz window. Another attractive characteristic of said reactors is obtaining large activation areas of the plasma. In this paper, we propose a microwave plasma reactor based on the TM 112 cylindrical mode, which is subject to a computational study. Unlike axisymmetric modes, which activate the plasma on the cavity axis, the TM 112 cylindrical mode presents two activation plasma areas. The reactor was designed following the methodology described by Silva et al., and using the Plasma, Radiofrequency (RF), and Heat transfer modules of the software COMSOL Multiphysics. The obtained results are presented in two stages. The first one is related to the initial electric field distribution of the TM 112 mode. Next, the generation of the hydrogen plasma was simulated from the interaction of H 2 gas with the TM 112 microwave field. The plasma activation process is described in detail from graphics of the time evolution of the electron density, hydrogen density, and their respective temperatures until a steady state is reached. Additionally, the influence of the pressure on the concentration and the temperature of both electrons and gas in a steady state is analyzed. The presented results can be useful for the design of plasma reactors for diamond deposition.